Photocatalytic Degradation of Toxic Pesticides: Mechanistic Insights - Oladipo, Akeem Adeyemi; Gazi, Mustafa; Ifebajo, Ayodeji Olugbenga; Oladipo, Adewale Sulaiman; Ahaka, Edith Odinaka (Wiley, 2020)
Pesticides are frequently used in agricultural fields to control weeds and pests; however, their excessive use has detrimental effects on the environment including a threat to endangered plant species. Notably, prolonged exposure to water containing-pesticides or agricultural lands runoff can cause adverse skin, neurological system related problems and cancer. Considering their high toxicity, persistence nature, and bio-accumulation potential, complete removal of pesticides from wastewater is vital. Treatment of water containing pesticides is often difficult by conventional methods due to their strong recalcitrant nature; therefore, this chapter focuses on the use of advanced oxidation processes (AOPs)which are efficient for elimination of most persistent organic pollutants. This chapter provides a brief overview of thepesticides’ potential risk of exposure in water, occurrences, and environmental fates, critical review of most recent research on the photocatalytic degradation of pesticides, commonly used photocatalysts, and fundamental characteristics of photocatalytic processes. Emphasis is also directed to the photocatalytic degradation mechanisms and pathways; as well as the challenges faced by this technology and its future prospects. © 2020 Scrivener Publishing LLC.
Keywords: endocrine-disrupting pollutants; pesticides; photobased-degradation pathway; photocatalysis mechanism; Photocatalytic degradation